Postharvest : an introduction to the physiology and handling of fruit and vegetables - Wills, R. B. H.; Golding, John Brett (CABI, 2016)
This book contains 12 chapters focusing on the basic tenets of postharvest technology of fruits and vegetables and how this influences their postharvest behaviour. Key information about their composition, biochemistry, respiration and physiology are presented. The importance of the management of temperature and humidity for maintaining fresh quality is discussed. The susceptibility of fresh produce to various pathogenic diseases and physiological disorders and their identification and control by environmentally friendly methods are pointed out and technologies that are adjuncts to temperature management, i.e. atmosphere control, controlled ripening, packaging and transport, are highlighted. The principles underlying the food safety based quality assurance systems that also meet environmental requirements are outlined. The influence of consumers on the marketing and storage of fruit and vegetables are also examined. Postharvest is an essential handbook for students, practitioners and growers waiting to understand the science and technology of the harvesting, handling, storage and transport of fruit and vegetables to the consumer. This sixth edition has been substantially revised to capture the current and future trends in postharvest technology, and to help the industry meet the constantly evolving needs and expectations of consumers.